The third-class genie - "Leeson, Robert" (Collins: London, 2000)
Alec's world changes when he meets Abu the genie! Disasters were leading two-nil on Alec's disaster-triumph scorecard when he slipped into the vacant factory lot, with Ginger Wallace hot on his heels, ready to destroy him. There was a catastrophe awaiting him at home too, and of course, school was yet another disaster area. But his luck seemed to be changing when he discovered a sealed beer can that was empty. Stranger still, when he held it up to his ear, he could hear a faint snoring ..
Keywords: English Fiction- Children stories